PERHITUNGAN JEMBATAN LAYANG (FLYOVER) DENGAN TIPE BOX GIRDER BETON PRATEGANG (PRESTRESSED CONCRETE) UNTUK PERTEMUANJALAN MAYOR ALIANYANG DAN JALAN SOEKARNO-HATTA KABUPATEN KUBU RAYA - Prasetya, Wiratama Adi; ., Elvira; Budi, Gatot Setya (Jurnal Mahasiswa Teknik Sipil Universitas Tanjungpura, 2016)
Projection of traffic current is increasing of vehicle volume every year and for reducing conflict of perpendicular in junction of Jalan Mayor Alianyang and Jalan Sukarno-Hatta in Kubu Raya regency. Flyover become a alternative solution and a plan that can be a Bridge class 1 that has load of plan traffic current 100% from total load before. With width of highways 7,00 m (double ways) then must uses 2 unit box girder shaped trapesium with extend of bridge 60 m with spesification : tall of girder 2,80 m, width of bridge 2 x 8,50 m, quality of prestressed concrete box girder K-500 (fc=41,50 MPa), and quality of plat concrete/slab of floor bridge K-500 (fc = 41,50MPa). It has 23 part in calculation proses and analysis flyover structure that must composed then can give of subscribing about applied of prestressed concrete structure in box girder section. Based on result of calculation and analisys of the first prestressing force is 85290,81 kN, it has total of loss prestressing 22,02 %, so remain of effective 50128,16 kn of prestressing force from jacking force result 64285,74 kN. Effective prestressing used 70%, it has 45000,02 kN of prestressing force of jacking force result 100% UTS is 113159,20 kN. In a box girder section uses prestressing tending consists: 28 tendon with spescification of diameter nominal strands 12,7 mm (0,5?), 22 wire with uncoated 7 wire kind of super strands ASTM A-416-06 grade 270 each 1 tendon and 14 tendon with specification of diameter nominal strands 12,7 mm (0,5?), 31 wire of kind uncoted 7 wire super strands ASTM A-416-06 grade 270 each 1 tendon. Then for longitudinal reinforcement in above of plat uses D19-200 mm, plat of wall or web section uses D19-150 mm, and plat of down in wall section uses D19-200 mm, stretch of reinforcement uses diameter is 16 mm with varian of distance in pillar area till a middle of span: 100 mm and 200 mm, eventough sum of crossbar that need for bursting force 5 D 16 mm in each 1 anchorage. Keywords : Flyover, Prestress, harian regional, Box Girder.